Adaptive Thermal Comfort in The Tropic: A Case Study of The Aceh Tsunami Museum - Laina Hilma Sari; Zulfian . (Graduate Program of Syiah Kuala University, 2013)
Abstract - Thermal comfort calculated using ISO 7730 has been questioned and responded by more adaptive thermal comfort methods. This study was therefore conducted to assess the acceptable thermal comfort for the local people in the tropical Aceh using the measurement based on ISO 7730 and with adaptive thermal comfort method by questionnaires. In this research, Aceh Tsunami Museum building, located in Banda Aceh, Indonesia, was in an open designed layout to be assessed as a case study. This study was conducted onsite using mechanical equipment and involving 138 respondents. The result shows that the comfort temperature calculated by mechanical equipment based on ISO 7730 is 23.140C. This is in contrast with the result of the questionnaires that showed people in an open building design rate the air temperature up to 320C as slightly cool. This condition is influenced by the mean air speed of 2.34 m/s and the mean relative humidity of 66.25%. This finding agrees that obtaining the comfort air temperature especially in tropics merely from the prediction of comfort index in ISO 7730 is inaccurate since the respondents actually could adapt with the higher air temperature. Keywords: Adaptive thermal comfort; Tropics; Aceh Tsunami Museum